IMPLEMENTATION OF THE SI CANTIK APPLICATION IN REDUCING THE MATERNAL AND CHILD MORTALITY RATE AT THE SIDOARJO REGENCY HEALTH OFFICE - Pitaloka, Icha Octavia Dyah; Mursyidah, Lailul (Proceeding of International Conference on Social Science and Humanity, 2025)
Objective: The research aims to analyze the implementation of the Sicantik application as an innovation in health information systems designed to improve maternal and child health services, particularly through enhanced monitoring and emergency referrals. Method: A descriptive qualitative approach was applied to identify factors influencing the effectiveness of the program, using data collected from observations, interviews, and documentation. Results: The findings reveal that the Sicantik application has contributed positively by increasing awareness and access to health services for pregnant women, thereby supporting efforts to reduce AKI and AKB. However, challenges persist, including limited technological understanding among health workers and insufficient government facility support, which hinder optimal utilization. Novelty: This study highlights the significance of integrating digital health innovations into maternal and child health services at the regional level, emphasizing that sustainable improvements require not only technological tools but also capacity building for health workers and stronger institutional support to ensure long-term effectiveness.